The Condition of Anarchism in the New International Order in the Middle East from 2011 to 2021 - Rebin Abdalrahman Fatah (Zanco Journal of Human Sciences, 2025)
This study focuses on a brief historical background of the concept of anarchism, its results and reactions, and also on the impact of this concept on the status of states in relation to each other's level of power and practical reality, especially after the events and changes witnessed by the Arab countries in 2011, which is that the weight of states and their position in their foreign policy contradicts the environment that guides their policy. The study also focuses on the environment of the international political system and the interaction and clashes of powers in the Middle East region, especially after the changes witnessed by the Arab countries in 2011, and the conflict of interests of states within the framework of revolutions and uprisings... All interactions and relations that take place between states are only to the extent necessary to convey the level of their impact on the instability present in the international system.